Analisis keterampilan berpikir kritis matematis ditinjau dari multiple intelligences pada peserta didik kelas V di sekolah dasar - Widi Ika Maryani; Retno Winarni; Anesa Surya (Didaktika Dwija Indria, 2023)
This study aims to explain and describe the ability to think critically mathematically in terms of Multiple Intelligence in fifth grade students at elementary school. The method used in this study is a qualitative approach with a case study research design. Sampling was carried out using purposive sampling technique. The data collection technique uses triangulation using data from document analysis, questionnaires, interviews, and observations. Data analysis was carried out descriptively and qualitatively. Based on the research results, it is known that the ability to think critically basically has different levels of ability when viewed from the perspective of multiple intelligences. Students have a lower level of critical thinking skills than their peers; However, they show extraordinary intelligence in certain areas. Students who fall into the categories of linguistic intelligence, musical intelligence, intrapersonal intelligence, and natural intelligence show lower order thinking skills (Lower Order Thinking/LOT) on mathematical critical thinking performance. Students with logical-mathematical intelligence and spacial intelligence category show High Order Thinking (HOT) on mathematical critical thinking performance. Students who fall into the category of bodily-kinesthetic intelligence and interpersonal intelligence show Middle Order Thinking (MOT) on mathematical critical thinking performance. This study focuses on the characteristics of students' multiple intelligences towards the level of critical thinking mathematics so that it can be used as a reference for classifying students in the process of learning mathematics.